Probing intermediate mass Higgs interactions at the CERN large hadron collider - Eboli, OJP; Gonzalez-Garcia, M. C.; Lietti, S. M.; Novaes, Sérgio Ferraz [UNESP] (Elsevier B.V., 2000)
We analyze the potentiality of the CERN Large Hadron Collider to probe the Higgs boson couplings to the electroweak gauge bosons. We parametrize the possible deviations of these couplings due to new physics in a model independent way, using the most general dimension-six effective lagrangian where the SU(2)(L) x U(1)(Y) is realized linearly. For intermediate Higgs masses, the decay channel into two photons is the most important one for Higgs searches at the LHC, We study the effects of these new interactions on the Higgs production mechanism and its subsequent decay into two photons. We show that the LHC will be sensitive to new physics scales beyond the present limits extracted from the LEP and Tevatron physics. (C) 2000 Elsevier B.V. B,V, All rights reserved.